Co-creative media: Capacity building with participatory communication to adopt good agricultural standards practice for people's health - Panida Jongsuksomsakul; Kevin Roebl (Research in Globalization, 2022)
The World Health Organization (WHO) has used communication methods to promote the international ban of the agricultural pesticides paraquat, glyphosate and chlorpyrifos. This ban has led to misunderstanding among farmers who still use these chemicals, which may be available under different brand names. Communication with the non-scientific community is uncertain leading to miscommunication, especially where scientific language is used. Governments have banned the use of these agricultural chemicals. The scientific arguments are not necessarily understood by famers so they may ignore the prohibition and continue using them or other similar chemicals. This study uses story-telling and qualitative research methods where a questionnaire is combined with the content analytical technique. The quantitative research method was used to collect data in the field where 351 participants took part. Participatory action research is a method where community farmers engaged in self-reflection on the impact of chemicals on their fields, their health and the health of others. Their understanding of the non-chemical usage model and good agricultural practice farmers in the vicinity, especially as they were personally involved in the creation of the media from script preparation, to acting, filming, and evaluating the final docu-dramas. The findings of the docu-drama programmes of 5 GAP farmers are presented to identify the perception of how to avoid using chemicals and their solutions for tangerine farmers through a manual that is the media output from the project and the resulting findings suggesting that the factors related to the effectiveness of scientific communication are divided into pull factors and push factors.
Keywords: 330; Co-Creative Media; Development Communication; GAP; PAR; Storytelling